MENCARI PERSPEKTIF TERORISME DI INDONESIA: - Arief Subhan (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
There is a strong perception among observers that Southeast Asia is a “second front” in the “global war on terrorism” —after Middle Eastern countries as the “first front”. Others have even suggested that this region is a “haven” for terrorism. Among the countries in the Southeast Asia —Thailand, Malaysia, Singapore, and the Philippines— Indonesia has special attention. Not only because Indonesia is a country with the largest Muslim population in the world —according to 2005 statistics, the country is inhabited not less than 208.819.86 soul with the percentage of more than 90 percent Muslim. Moreover, and perhaps more importantly, because of the Jemaah Islamiyah (JI), which was identified as the al-Qaeda network of localglobal Muslim organization under the command of Osama Bin Laden in Southeast Asia, not only initiated by Muslim Indonesia, but also gain fertile ground for growth. This paper seeks to provide an explanation of terrorism, social and political background of the emergence of terrorism in the Muslim world, and radical Islamist groups that contribute to the emergence of militant attitude among some Muslim countries, including Indonesia. KEY WORDS:Terrorism, Southeast Asia, Jemaah Islamiyah, al-Qaeda network, radical Islamist group, Collective Action Theory.